1997
DOI: 10.1093/carcin/18.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic DNA adducts in foundry workers in relation to exposure, life style and CYP1A1 and glutathione transferase M1 genotype

Abstract: Levels of aromatic DNA adducts in foundry workers and controls were followed at four annual samplings. During this time exposure to polycyclic aromatic hydrocarbons (PAH) decreased and the level of DNA adducts decreased accordingly. In the total group exposure was related to the level of adducts. Adduct levels correlated with urinary 1-hydroxypyrene (LOGU1OH), air benzo[a]pyrene, weekly working hours and daily cigarette consumption. In a multivariate model 1-hydroxypyrene had a consistent effect. Neither gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 13 publications
4
34
2
Order By: Relevance
“…The saturation of enzymes may be a reason for this reverse relationship (Vineis and Martone, 1995;Garte et al, 1997). This is supported by Merlo et al (1998) who found a significant correlation between CYP1A1 Msp1 and 1-OHP excretion at low levels of exposure to PAHs and by Hemminki et al (1997) who showed a significant increase of DNA-adducts at low levels of PAH exposure, similar findings having been reported by Georgiadis et al (2001). The results for our low PAH exposure group, the controls, were in good agreement with the results reported by the aforementioned authors.…”
Section: Discussionsupporting
confidence: 93%
“…The saturation of enzymes may be a reason for this reverse relationship (Vineis and Martone, 1995;Garte et al, 1997). This is supported by Merlo et al (1998) who found a significant correlation between CYP1A1 Msp1 and 1-OHP excretion at low levels of exposure to PAHs and by Hemminki et al (1997) who showed a significant increase of DNA-adducts at low levels of PAH exposure, similar findings having been reported by Georgiadis et al (2001). The results for our low PAH exposure group, the controls, were in good agreement with the results reported by the aforementioned authors.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously reported a lack of association between DNA adducts and urinary 1-HOP in garage workers exposed to automobile exhaust (38), but the adduct level correlated with urinary 1-HOP in foundry workers (31). Similarly, as in our observation for DNA adducts, we did not observe any correlation between urinary 1-HOP and the PAH-albumin adduct level.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, no difference in DNA adduct level could be observed in street vendors in Milan, Italy, working in areas of high and low traffic density (30). However, the Italian study included both smokers and nonsmokers, and smoking is known to increase the adduct level (31). In the present study an interesting effect of the PMBC composition was observed, as individuals with a high content of B lymphocytes had a lower DNA adduct level.…”
Section: Discussioncontrasting
confidence: 67%
“…A similar discrepancy in DNA adduct results has been found also for coke workers extensively exposed to PAH. The levels of PAH in foundries and bus garages have been much lower than for potroom workers, but increased DNA adduct levels have nevertheless been observed (33). Variation in the size distribution of the inhaled particles may be a contributing factor to these apparently contradictory findings.…”
Section: Discussionmentioning
confidence: 97%